THERAPEUTICAL ASPECTS IN CONVENTIONAL REMOVABLE TREATMENT - Bosinceanu, Dan Nicolae; Forna, Norina Consuela; Bosinceanu, Dana (European Scientific Journal, ESJ, 2014)
Conventional dentures represent the most common prosthetic solution for edentulousness, therefore they should reestablish all functions of masticatory system considering the changes caused by the age and edentation.This paper aims to assess every possibility to reconstruct the edentulous arches in order to recover all functions, the study being conducted on a group of 46 patients,adopting an individualised treatment plan for each other.